The cost of health care in Serbia according to the international classification of diseases for the period from 2004 to 2009 - Gajić-Stevanović Milena; Dimitrijević Snežana; Živković Slavoljub; Teodorović Nevenka; Perišić-Rajnicke Darinka (Serbian Medical Society - Dental Section, Belgrade, 2011)
Introduction. As the part of research on costs in the health care system, there is a growing interest in the world for the estimating costs for the treatment of disease. This value represents the burden that a particular disease or group of diseases puts on the society. Until the year 2000, when the Organization for Economic Countries Development (OECD) established a System of Health Accounts (SHA), there was not even approximate methodological guide for calculating the cost of the disease. The aim of this study was to determine the costs of health care in the Republic of Serbia according to the major International Classification of Diseases (ICD-10) and to provide a comparative cost analysis for the treatment of diseases in the period from 2004 to 2009. Material and Methods. A retrospective and comparative analysis of health statistics from the database of the Institute of Public Health of Serbia and financial information provided by the Health Insurance Fund in the period 2004-2009 was performed. Financial information and data on hospital services, outpatient, home health care, ancillary health care services, drug consumption and consumer goods in healthcare were analyzed using SHA methodology. Results. Results showed that during the observation period, the maximum cost of health care in Serbia by main classification of ICD-10 was achieved in 2009 and it was RSD 144,150,456,906.00 (€ 1,503,321,134; $ 2,160,253,219) and the minimal cost was achieved in 2004 - the amount being RSD 49,546,211,470.00 (€ 628,086,723; $ 855,203,134). Results showed that in 2004 the highest costs were allocated to circulatory diseases (18.98%), followed by neoplasm (11.12%), and lowest for congenital anomalies (0.64%). In 2009, the highest costs were allocated to circulatory diseases (18.87%), infectious and parasitic diseases (11.20%), diseases of digestive system (9.26%) nervous system diseases (9.20%), and neoplasm (8.88%), whereas the minimal funds were allocated for congenital anomalies (0.33%). Conclusion. Comparative analysis showed that the value of overall spending in healthcare increased three times in 2009 as compared to 2004.